Optimizing yard space for independent food security in Kebonbatur Village - Slamet Budirahardjo; Setyoningsih Wibowo (Universitas Muhammadiyah Magelang, 2024)
Amidst economic hardships and rising staple food prices, the majority of residents in RT 01 RW III of Kebonbatur Village, Mranggen District, Demak Regency, who work as laborers and farmers, struggle to meet their daily food needs. This community service program aimed to optimize limited yard space by introducing urban farming using the BUDIKDAMBER system (fish and vegetable cultivation in buckets). The training covered equipment preparation, fish distribution techniques, feeding, water quality maintenance, fish harvesting, and vegetable planting using aquaponics methods. Intensive mentoring was provided to ensure practical implementation of the acquired knowledge. The residents' enthusiasm was remarkable, as they immediately applied the learnings in their respective yards. This activity successfully raised awareness and skills among residents in utilizing limited space for self-reliant food security, as evidenced by active participation, satisfaction with harvest results, and the opening of economic opportunities.